Kajian Parameter 3D Printing Terhadap Ketangguhan Material dan Kualitas Permukaan Menggunakan Metode Taguchi - Muhammad Arifin (Universitas Harapan Medan, 2023)
3D Printing Fused Deposition Modeling (FDM) is the printing of thermoplastic material layer by layer to form a three-dimensional product in which the adhesion between layers must be well controlled to obtain high mechanical performance and product integrity. The research aims to investigate the influence of the nozzle temperature, table temperature, and filling model on the mechanical strength and surface quality of the product. The PLA filament used in this study, the experimental data capture design using the Taguchi L9 with factor and level (2)4 two nozzle temperature parameters, two model infill parameters, two print speed parameters, and printer table temperature. The durability and quality of the product are the focus of this compilation, and data analysis using robust statistical methods of S/N Ratio design. The relationship of rigidity to mechanical force is also discussed. The temperature of the nozzle becomes a major influence on the firmness of the product for the surface hardness which is a big influence not of the temperature but of the model of the infill